2022
DOI: 10.53854/liim-3003-3
|View full text |Cite
|
Sign up to set email alerts
|

MIS-C related to SARS-CoV-2 infection: a narrative review of presentation, differential diagnosis, and management

Abstract: Multisystem Inflammatory Syndrome in Children (MIS-C), a rare condition, has been reported approximately 2-4 weeks after the onset of COVID-19 in children and adolescents, causing inflammation in multiple systems, including cardiovascular and respiratory, digestive, and central nervous systems. This condition is also known as hyperinflammatory shock, Kawasaki-like disease, and Pediatric Inflammatory Multisystem Syndrome (PIMS). The signs and symptoms include but are not limited to fever, rash, peripheral edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…The majority of our patients showed elevated inflammatory markers, including CRP (greater than 5 mg/dL in 98.7%), ESR (greater than 20 mm/hr in 92.5%), and ferritin levels (greater than 400 μg/L in 70%), consistent with immune dysregulation-induced cytokine storm and consistent with those found in the literature [3,21]. Lymphopenia in our study was reported in 72.5% of patients, higher than reported by Mamishi et al (54%) and (64%) by Lee et al [19,22]. Lymphopenia was statistically evident in patients younger than five years old (p-value = 0.001), contrary to that reported by Feldstein et al [9], where lymphopenia was more pronounced in older patients.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of our patients showed elevated inflammatory markers, including CRP (greater than 5 mg/dL in 98.7%), ESR (greater than 20 mm/hr in 92.5%), and ferritin levels (greater than 400 μg/L in 70%), consistent with immune dysregulation-induced cytokine storm and consistent with those found in the literature [3,21]. Lymphopenia in our study was reported in 72.5% of patients, higher than reported by Mamishi et al (54%) and (64%) by Lee et al [19,22]. Lymphopenia was statistically evident in patients younger than five years old (p-value = 0.001), contrary to that reported by Feldstein et al [9], where lymphopenia was more pronounced in older patients.…”
Section: Discussionsupporting
confidence: 91%
“…A fifth limitation of the study is that multi-inflammatory syndrome in childhood (MIS-C) as one of the differential diagnoses in a child with COVID-19 was not entirely ruled out [3]. According to the WHO diagnostic criteria for MIS-C, the following six criteria must be met: 1) age <20y, 2) fever >2 days, 3) clinical signs of multisystem involvement, 4) elevated inflammatory markers, 5) no other obvious microbial cause of inflammation, and 6) confirmed SARS-CoV-2 infection [4].…”
Section: Dear Editormentioning
confidence: 99%